Implikasi Kertoaji sebagai Pendekatan Tradisional dalam Pembagian Warisan terhadap Hubungan Kekeluargaan di Desa Sananrejo, Kecamatan Turen, Kabupaten Malang, Jawa Timur - Putra Pandu Dinata Nurdiansyah; Zaenul Mahmudi (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The practice of inheritance distribution plays a crucial role in maintaining family harmony and social stability. This study aims to analyze the traditional inheritance distribution practice in Sananrejo Village, Turen Subdistrict, Malang Regency, through the